Benchmark Performance of Emergency Medicine Residents in Pediatric Resuscitation: Are We Optimizing Pediatric Education for Emergency Medicine Trainees?. Issue 2 (23rd September 2020) - Schoppel, Kyle A.; Stapleton, Stephanie; Florian, Jana; Whitfill, Travis; Walsh, Barbara M.
Abstract: Background: The majority of children in the United States seek emergency care at community‐based general emergency departments (GEDs); however, the quality of GED pediatric emergency care varies widely. This may be explained by a number of factors, including residency training environments and postgraduate knowledge decay. Emergency medicine (EM) residents train in academic pediatric EDs, but didactic and clinical experience vary widely between programs, and little is known about the pediatric skills of these EM residents. This study aimed to assess the performance of senior EM residents in treating simulated pediatric patients at the end of their training. Methods: This was a prospective, cross‐sectional, simulation‐based cohort study assessing the simulated performance of senior EM resident physicians from two Massachusetts programs leading medical teams caring for three critically ill patients. Sessions were video recorded and scored separately by three reviewers using a previously published simulation assessment tool. Self‐efficacy surveys were completed prior to each session. The primary outcome was a median total performance score (TPS), calculated by the mean of individualized domain scores (IDS) for each case. Each IDS was calculated as a percentage of items performed on a checklist‐based instrument. Results: A total of 18 EM resident physicians participated (PGY‐3 = 8, PGY‐4 = 10). Median TPS for the cohort was 61% (IQR = 56%–70%). Median IDSs by case were as follows: sepsis 67% (IQR = 50%–67%), seizure 67% (IQR = 50%–83%), and cardiac arrest 67% (IQR = 43%–70%). The overall cohort self‐efficacy for pediatric EM (PEM) was 64% (IQR = 60%–70%). Conclusions: This study has begun the process of benchmarking clinical performance of graduating EM resident physicians. Overall, the EM resident cohort in this study performed similar to prior GED teams. Self‐efficacy related to PEM correlated well with performance, with the exception of knowledge relative to intravenous fluid and vasopressor administration in pediatric septic shock. A significant area of discrepancy and missed checklist items were those related to cardiopulmonary resuscitation and basic life support maneuvers.